Immune and Hormonal Response to High-intensity Exercise During Orienteering - Araujo, Nayara Costa; Neto, Anibal Monteiro Magalhães; Fujimori, Mahmi; Bortolini, Miguel Sordi; Justino, Allisson Benatti; Honorio-França, Adenilda Cristina; Luzía França, Eduardo (International Journal of Sports Medicine, 2019)
Orienteering is an endurance sport that combines physical and cognitive activity, during which the athlete must complete a course with several points distributed over unknown terrain in the shortest possible time. A number of studies have investigated the body’s physiological adaptations to the stress caused during competition, but not the immunological changes. To that end, the present study evaluated the immunological, physiological and pathological responses in athletes performing high-intensity physical exercise during an orienteering race. The 30 athletes tested belonged to the elite orienteering category and participated in the regional championship. Cortisol levels were determined before and after the competition to assess stress response, as were the cytokines IL-2, IL-4, IL-6, IL-10, TNF-α, IFN-γ and IL-17 to evaluate the immune response. Cortisol levels increased after the competition, indicating a stress condition. IFN-γ, IL-6 and IL-10 levels also rose post competition. The results indicate that orienteers are exposed to high stress levels, and that this condition affects their immune and endocrine systems, triggering a predominantly anti-inflammatory response, likely an athlete’s mechanism of adaptation to the stress imposed by high-intensity physical exercise.
Keywords: cytokines; cortisol; endurance race; orienteering